(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article is devoted to teaching the topic of plane in engineering graphics; some teaching methods are presented. Examples from real life are given where the intersection of planes, parallel planes, and the intersection of a straight line and a plane are used.